Virtual teams : practical guide to wikis and other collaboration tools - Todorov, Valentin (UNIDO ViennaAT, 2010)
Provides an overview over the strengths and weaknesses of wikis as a tool for collaboration; an introduction of the concept of wikis; brief overview on technical characteristics of wikis; the historical and social context of the emergence of wikis; and a comparision of wikis to other collaboration tools like mailing list, forums and blogs, paying particular attention to points characteristic in wikis.